Pembuatan Bahan Bakar Padat Dari Pelepah Sawit Dengan Menggunakan Gliserol Sebagai Perekat - Firman Tampubolon; Zuchra Helwani; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Biomass is currently the largest renewable energy source globally and economically and also an environmentally friendly energy source. One of the potential agricultural wastes that can be used as an alternative fuel is oil palm fronds. The heating value of oil palm fronds is 17.200 kJ/kg. The heating value can be improved by conducting carbonization process followed by densification. With carbonization the smoke forming elements can be minimized, so that the exhaust gas is cleaner. Biomass densification aims to increase density and reduce handling problems such as storage and transportation. The heat value can be increased again by adding an adhesive in the form of glycerol which has a heating value 25.175 kJ/kg. The aim of this study is to produce a solid fuel from oil palm fronds by using carbonization process and to know the characteristics of products. This study aims to produce solid fuel using the densification process of oil palm fronds carbon obtained from the carbonization process, knowing the effect of adhesive composition and compacting pressure in the manufacture of products and knowing the heating value of the products produced. The particle size used where 20 mesh and the adhesive composition used where 90:10, 80:20 and 70:30 %wt. Compacting pressure used where 50, 75 and 100 bar. Data processing in this study was obtained by proximate analysis, density, and using a bomb calorimeter. The highest heating value obtained was 24.604 kJ/kg from the briquette product with the adhesive composition 70:30 and the compacting pressure 50 bar. While for the lowest heating value obtained at 20.693 kJ/kg on briquettes which adhesive composition 90:10 and compacting pressure 100 bar. Process conditions that have a significant effect on heating value are adhesive compositions and compacting pressures.Keywords: densification, glycerol, carbonization, heating value, oil palm fronds